A comparative analysis of EMG according to increasing numbers of pitches in youth baseball pitcher - Park, I. B. (Korean Journal of Sport Biomechanics, 2025)
Objective: This study aimed to analyze changes in upper extremity muscle activation during repeated pitching by youth baseball players and to provide foundational data for injury prevention and training enhancement by assessing the impact of fatigue on electromyographic (EMG) signals.